1992
DOI: 10.1093/carcin/13.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic stimulation of hepatocellular proliferation in rodents following 1,4-dichlorobenzene administration

Abstract: 1,4-Dichlorobenzene (DCB), a non-DNA-reactive compound, induced hepatocellular carcinomas at 600 mg/kg/day, but not 300 mg/kg/day in male and female B6C3F1 mice in a National Toxicology Program (NTP) bioassay. Cell proliferation studies were performed under conditions of the NTP bioassay to determine the mode of DCB-induced hepatocellular proliferation and whether this proliferative response may be related to the carcinogenic activity of DCB. The percentage of cells in S-phase (labeling index; LI) was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 0 publications
7
35
0
1
Order By: Relevance
“…In the rat, liver weight and liver hypertrophy were clearly increased by DEHP, CINN and DCB, as reported by others (30)(31)(32). MON, ETU, and LIM also gave weak increases in liver weight that were sometimes accompanied by liver hypertrophy.…”
Section: Ratsupporting
confidence: 82%
See 3 more Smart Citations
“…In the rat, liver weight and liver hypertrophy were clearly increased by DEHP, CINN and DCB, as reported by others (30)(31)(32). MON, ETU, and LIM also gave weak increases in liver weight that were sometimes accompanied by liver hypertrophy.…”
Section: Ratsupporting
confidence: 82%
“…The noncarcinogens CINN, DCB, ETU, TMTU, and LIM also gave increases in labeling index; only DETU had no effect. Increases in labeling index produced by some of these compounds have been shown previously (27,30,31,34). All of the compounds tested gave increases in cytochrome P450, determined either as total (spectral) P450 or as specific isoforms (Western blots).…”
Section: Ratsupporting
confidence: 60%
See 2 more Smart Citations
“…Medical case reports on the health of p-DCB-exposed humans [5][6][7][8][9][10] revealed that clinical signs and symptoms induced by excessive exposure were central nervous system effects, eye and nose irritation and hepatic, renal and hematological disorders. Studies on experimental toxicology demonstrated that p-DCB induced hepatic, renal and hematological toxicity in mice and rats 6,[11][12][13][14][15][16][17][18][19][20][21][22][23] . Toxicity data from the inhalation exposure of experimental animals to p-DCB vapor are more relevant for assessing the health risks of p-DCB-exposed humans than those from oral administration because inhalation exposure is the principal route of humans, exposure to p-DCB.…”
mentioning
confidence: 99%